(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The development of the marine renewable energy, as referenced in the objectives achievement of many energy roadmaps [1], is conditioned by the possibilities to integrate the marine generation power plants in the electric systems. Offshore wind, floating solar PV, tidal, waves and even saline gradient are the technologies considered. The success of these plans needs to fulfil, among others, the compliance of the electric grid codes, ensuring the stability of electric grids. The integration of marine renewable energies is still not a problem at the electric grids, since the penetration level is not so high. However, the objectives established in the roadmaps invite to analyse the expected effects of new power plants from the point of view of performance at the electric systems. Actually, some research works have identified an increase in the number of frequency and voltage events in electric systems due to higher penetration of marine energies [2]. The connection of the marine renewable generation is usually taken place in nodes of the electric grids not very favourable in terms of power capacity and voltage drops. Moreover, many of the locations where the marine renewable energies result economically viable are linked to weak areas of the electric grid, meaning that frequency and voltage are more sensible. That is the case of remote isolated areas, as usually coastal areas, or islands. Additionally, some of the technologies considered, such as wave energy, present very oscillatory power profiles which produce an unbalance with the consumption profiles, leading to stability problems. More and more countries are putting an eye on new sources of energy, integrating them in their energy policies in order to search alternatives to face energy crisis. This is the case of many countries in Centre and South America, that have included in their roadmaps the renewable marine energies [3]. One of the main issues in these countries is the lack of robust electric grids or the condition of weak grids in coastal areas. This paper presents the result of the analysis of different electric grids in Ibero-American countries. Three different regions have been considered: Mesoamerica, South America and Iberian Peninsula and Macaronesia, and particular areas or countries have been selected from each region as representative of the critical conditions in terms of grid integration. Costa Rica, Peru, Brazil and Argentina, and the Canary Islands in Spain, are the selected case studies. The results presented will summarize: power limits, time response, energy storage and backup generation requirements, power ramps, power oscillation allowed, etc. This work has been accomplished in the frame of the activities carried out by the groups involved in the thematic network REMAR (Opportunities of Integration of Ocean Energies in Ibero-American Electric Grids), promoted and funded by the Ibero-American Programme of Science and Technology for the Development (CYTED).